Outcomes of Male Patients with Alport Syndrome Undergoing Renal Replacement Therapy - Temme, Johanna (American Society of Nephrology, 2012)
BACKGROUND AND OBJECTIVES: Patients with the hereditary disease Alport syndrome commonly require renal replacement therapy (RRT) in the second or third decade of life. This study compared age at onset of RRT, renal allograft, and patient survival in men with Alport syndrome receiving various forms of RRT (peritoneal dialysis, hemodialysis, or transplantation) with those of men with other renal diseases. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Patients with Alport syndrome receiving RRT identified from 14 registries in Europe were matched to patients with other renal diseases. A linear spline model was used to detect changes in the age at start of RRT over time. Kaplan-Meier method and Cox regression analysis were used to examine patient and graft survival. RESULTS: Age at start of RRT among patients with Alport syndrome remained stable during the 1990s but increased by 6 years between 2000–2004 and 2005–2009. Survival of patients with Alport syndrome requiring dialysis or transplantation did not change between 1990 and 2009. However, patients with Alport syndrome had better renal graft and patient survival than matched controls. Numbers of living-donor transplantations were lower in patients with Alport syndrome than in matched controls. CONCLUSIONS: These data suggest that kidney failure in patients with Alport syndrome is now being delayed compared with previous decades. These patients appear to have superior patient survival while undergoing dialysis and superior patient and graft survival after deceased-donor kidney transplantation compared with patients receiving RRT because of other causes of kidney failure.